2016
DOI: 10.1016/j.cjtee.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Are falls more common than road traffic accidents in pediatric trauma? Experience from a Level 1 trauma centre in New Delhi, India

Abstract: PurposeThe epidemiology of pediatric trauma is different in different parts of the world. Some researchers suggest falls as the most common mechanism, whereas others report road traffic accidents (RTAs) as the most common cause. The aim of this study is to find out the leading cause of pediatric admissions in Trauma Surgery in New Delhi, India.MethodsInpatient data from January 2012 to September 2014 was searched retrospectively in Jai Prakash Narayan Apex Trauma Centre Trauma Registry. All patients aged 18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
4
13
0
1
Order By: Relevance
“…In the present study, there were 17 boys (60.71%) and 11 girls (39.29%). Similar preponderance of males was found in studies conducted by Ghilley SK et al 13 (64% boys and 36% girls), Baig MS et al 10 (73.3% boys and 26.7% girls), Tandon T et al 14 (54.8% boys and 45.2% girls), Babu A et al 15 (78.6 % were males and 21.3 % were females) and Arora R et al 12 (67% males, 33% females). Male preponderance in all these studies can be attributed to higher level of activity among male children as compared to female children.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, there were 17 boys (60.71%) and 11 girls (39.29%). Similar preponderance of males was found in studies conducted by Ghilley SK et al 13 (64% boys and 36% girls), Baig MS et al 10 (73.3% boys and 26.7% girls), Tandon T et al 14 (54.8% boys and 45.2% girls), Babu A et al 15 (78.6 % were males and 21.3 % were females) and Arora R et al 12 (67% males, 33% females). Male preponderance in all these studies can be attributed to higher level of activity among male children as compared to female children.…”
Section: Discussionsupporting
confidence: 84%
“…In a study by Singh O et al, 16 59.40 % patients had history of fall, followed by road traffic accident (32%). Baig MS et al 10 and Babu A et al 15 found the predominant cause to be road traffic accidents. Many other studies also found road traffic accidents to be the predominant cause.…”
Section: Discussionmentioning
confidence: 98%
“…31 This was however in contrast to study by Babu et al and Kundal et al where they found RTA to be the leading cause of trauma, however their study was in predominantly urban set up. 32,33 Incidence of assault injury was slightly higher among female paediatric population compared to male child; this might be because of the girl child are not as preferred as the male child in this part of the country.…”
Section: Discussionmentioning
confidence: 94%
“…There are also accounts of children falling from poorly constructed balconies and windows of which the majority dies and the remaining suffering serious injuries with potential for a long-term disability [27]. In India it was reported that fall from height is the second cause of pediatric head injury next to RTAs [51][52][53]. Incidents of RTAs involving children and teenagers in LMICs are markedly high as compared to the high income countries [54].…”
Section: Common Causes Of Trauma To Children In the Lmicsmentioning
confidence: 99%